Problematika Penyelesaian Sengketa Tanah Adat Melalui Hukum Adat di Desa Lumban Ruhap, Kecamatan Habinsaran, Kabupaten Toba, Provinsi Sumatera Utara - Hotni Br Nainggolan; Rosnidar Sembiring; Maria Kaban (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to examine the problems of resolving customary land disputes through customary law in Lumban Ruhap Village, Habinsaran District, Toba Regency, North Sumatra Province. The customary land disputes that occur create legal uncertainty regarding the status and ownership of land for the local customary community. The problem formulation in this study includes the causes of customary land disputes, the resolution process through customary law mechanisms, and the obstacles encountered in that process. The research method used is empirical juridical-legal research with a descriptive-analytical nature. The approaches used include sociological approaches and legislative approaches. Data were obtained through field interviews and literature studies, then analyzed qualitatively and descriptively. The results of the study indicate that customary land disputes are caused by unclear legal status and land ownership, unclear boundaries between customary land and private land, population growth, and increasing public awareness of the economic value of land. Dispute resolution is carried out through customary deliberations led by natua-tua ni huta involving the disputing parties and the local community. However, the settlement process often faces obstacles, including the parties’ absence, a lack of good-faith efforts to reconcile, limited witnesses and evidence, and unclear boundaries and land ownership.